Pollution, Health and Life Expectancy: How Environmental Policy Can Promote Growth - Xavier Pautrel (Fondazione Eni Enrico Mattei (FEEM), 2007)
This article investigates the influence of environmental policy on growth assuming that the channel of transmission relies on the link between pollution, health and the survival probability, in an overlapping generations model à la Blanchard (1985) where growth is driven by a mechanism à la Romer (1986). We demonstrate that environmental policy has an ambiguous effect on growth in the steady-state when the detrimental impact of pollution on health and lifetime is taken into account: for low levels of taxation, environmental policy promotes growth while it is harmful to growth for high levels. Furthermore, we show that the environmental policy is more likely to promote growth (i.e. it stimulates growth for a wider range of environmental taxes) when public expenditures in health and/or the impact of pollution on health are important. Finally, using numerical simulations, we find that for the value of parameters chosen the environmental policy will be more likely to harm growth when agents smooth consumption over time.
Keywords: 330; Growth; Environment; Overlapping generations; Umweltpolitik; Umweltbelastung; Wirtschaftswachstum; Overlapping Generations; Theorie